Psychological Impact of Distance Learning on Children and Adolescents in Saudi Arabia: A Multi-City Analysis of Behavioral and Mental Health Outcomes During the COVID-19 Pandemic - Samah H. Alkhawashki; Maram H. AlTuwairqi; Ahmad H. Almadani; Afnan A. Almarshedi; Rahaf Alasiri; Noha A. Mobeireek; Mishaal R. Alrashoud; Noura A. Abouammoh; Fatimah S. Alshahrani; Areej A. AlFattani; Shuliweeh Alenezi (Children)
Background: The COVID-19 pandemic triggered a global transition to distance learning, which significantly impacted children’s mental health. In Saudi Arabia, remote education began on 8 March 2020, lasting between 1.5 to 2.5 years. This study aims to explore the psychological effects of distance learning on children and adolescents, with a focus on mental health challenges and coping mechanisms. Methods: A cross-sectional study was conducted using an online survey distributed to parents of children aged 6 to 18 in the major metropolitan areas of Jeddah and Riyadh. The survey included demographic questions and the Arabic version of the Vanderbilt ADHD Diagnostic Rating Scale, a tool for assessing behavioral challenges, anxiety, and symptoms of attention deficit hyperactivity disorder (ADHD). Results: A total of 71.6% of families reported a positive experience with distance learning. A significant correlation was found between parents’ marital status and children’s ability to cope with remote education. Interestingly, children without ADHD symptoms experienced three times more negative outcomes than those with ADHD symptoms. However, despite reporting fewer negative experiences, children with ADHD exhibited increased symptom severity and academic difficulties. Of the students, 5.4% were diagnosed with predominantly inattentive ADHD, 1.8% with predominantly hyperactive/impulsive ADHD, and 3.9% with combined ADHD. Additionally, 7.2% of students screened positive for oppositional defiant disorder, 1.5% for conduct disorder, and 6.6% for anxiety or depression. Children from separated or divorced families were more likely to exhibit ADHD symptoms (p = 0.002). Children with ADHD symptoms reported a more positive experience with distance learning (p < 0.05). Conclusion: This study represents the first comprehensive, multi-city investigation in Saudi Arabia examining the relationship between distance learning, sociodemographic factors, and mental health symptoms in children. The findings highlight the psychological challenges faced by children during the pandemic and emphasize the need for targeted interventions to support both mental health and academic outcomes. These results offer valuable insights for future research and inform strategies to address children’s well-being in scenarios involving distance learning.